Assessing Fast-Food Restaurant’s Productivity in Rural Area Through Customer Waiting Time and Worker’s Efficiency - Abdul Latif, Nurul Najihah; Zainal, Maisarah; Mohd Haris, Nur Farihah; Shafie, Shahira; Misiran, Masnita; Md Yusof, Zahayu (Academic Inspired Network, 2019)
Fast food restaurant is known for its role in providing quick meals for the masses, thus it is critical to ensure the customer’s waiting time and employee’s efficiency match with its function. However, in the rural area, such issue has yet to be fully implemented. The general quality control practiced for restaurants in Malaysia aim to complete order within (maximum time) 5 minutes, thus this study would like to investigate whether such quality control is also visible in the franchise of the smaller town. This study shows long duration of customers’ waiting time (average time of 9.09 minutes on Tuesday and 24.19 minutes on Saturday) and low level of employees’ efficiency (55% on Tuesday and 20.67% on Saturday) in this restaurant. Initiatives such as self-service ordering kiosk and free Wi-Fi can improve customers’ perception towards the service in this restaurant